A Copper Complex of a Noninnocent Iminophenol‐Amidopyridine Hybrid Ligand: Synthesis, Characterization, and Aerobic Alcohol Oxidation. Issue 35 (12th November 2014) - Alaji, Zahra; Safaei, Elham; Chiang, Linus; Clarke, Ryan M.; Mu, Changhua; Storr, Tim
Abstract: Reaction of the noninnocent iminophenol‐iminopyridine hybrid ligand HL IPIP, where L IPIP denotes [2‐(( E )‐( E )‐2‐[( E )‐pyridin‐2‐ylmethyleneamino]benzylideneamino)‐4, 6‐di‐ tert ‐butylphenolate], with copper acetate afforded a copper complex, L APIP Cu II, in which one of the imine functional groups is oxidized to an amide during metal complexation. The new Cu II complex is capable of catalyzing efficient aerobic alcohol oxidation under mild conditions. The crystal structure of L APIP Cu II exhibits a square‐planar geometry with the Cu II center coordinated by three nitrogen atoms and one oxygen atom. Electrochemical studies were conducted to evaluate the redox‐active behavior of the complex, and the results showed a quasireversible reduction and a ligand‐based oxidation process. The neutral species of L APIP Cu II is EPR active, which is consistent with a paramagnetic electronic ground state (d 9, S = 1/2), whereas the one‐electron oxidized complex was X‐band EPR silent. One‐electron chemical oxidation of L APIP Cu II gave a new species that can be attributed to a Cu II ‐phenoxyl radical complex. Based on EPR measurements in conjunction with density functional theory calculations, [L APIP Cu II ] + is proposed to have a triplet electronic ground state, exhibiting a weak ferromagnetic interaction between the Cu II center and the coordinated phenoxyl radical. Abstract : A new copper complex of a noninnocent iminophenol‐pyridine hybrid ligand that is capable of efficient aerobic alcohol oxidation was studied.